Longitudinal change in spatiotemporal gait symmetry after discharge from inpatient stroke rehabilitation. Issue 5 (27th February 2020) - Rozanski, Gabriela M.; Wong, Jennifer S.; Inness, Elizabeth L.; Patterson, Kara K.; Mansfield, Avril
Abstract: Purpose: To describe the change in spatiotemporal gait asymmetry after discharge from stroke rehabilitation and examine the relationship with change in other clinical outcome measures. Methods: Secondary analysis of a prospective cohort study was conducted. Swing time and step length symmetry, balance, mobility, gait speed, and motor impairment were assessed at discharge and 6 months later. Participants ( n  = 61) were classified by shift in symmetry status (Asymmetric-to-Symmetric, Symmetric-to-Asymmetric, No Shift) and magnitude of difference scores (Improved, Worse, No Difference). Correlations between change in spatiotemporal symmetry and the other clinical measures of physical status were calculated. Results: At discharge, 61% (37/61) and 36% (22/61) of participants were asymmetric in swing time and step length, respectively. Of this subgroup, 43% (16/37) and 50% (11/22) shifted to symmetric gait by follow-up. In contrast, only six individuals significantly improved in swing and/or step symmetry according to minimal detectable change. Change in spatiotemporal symmetry was not significantly correlated with change in the clinical outcome measures. Conclusions: Despite overall gains in physical function and decreased prevalence of asymmetry, most individuals with stroke do not improve in swing or step symmetry following discharge from rehabilitation. Further research is necessary to elucidate factors that affect recovery of gait quality. Implications for rehabilitation: Asymmetric gait after stroke is a major concern for patients and their therapists but can be resistant to intervention. Spatiotemporal asymmetry persists for many individuals following discharge from hospital stay despite improvement in other gait-related measures. While the determinants of change remain unclear, gait quality should be specifically monitored and addressed to avoid long-term negative effects.